Vassilis Evangelidis, The Archaeology of Roman Macedonia. Urban and Rural Environments. - Donev , Damjan (Journal of Greek Archaeology, 2024)
A new book on the archaeology of Roman Macedonia should not occasion too much apologetics. As pointed out by Grigoropoulos in the Introduction, there still lacks an integrated study of the archaeology of Roman Macedonia, comparable to those of the neighbouring provinces. Because it rarely came into the focus of scholarly research, very little is known about the archaeological heritage of Roman Macedonia, and what is known so far, is not easily synthesized. Admittedly, in the Foreword, the author hastens to explain that the scope of this book is limited to the built environment, both urban and rural, and does not aspire to provide an overarching synthesis of economic life and society in Roman Macedonia. This is also implied in the book’s subtitle. In other words, this book is concerned primarily with the built heritage of Roman Macedonia, created in the period between the Roman conquest and the early 4th century AD. But even if it falls short of fulfilling Grigoropoulos’ vision of an integrated study of the history and archaeology of Roman Macedonia, the study by Evangelidis is a most-welcome addition to the existing corpus of studies on Roman Macedonia.